Analisis Pemanfaatan Media Sosial Instagram Dalam Membangun Corporate Image PT Suvarna Jakarta Golf Club - Siti Masitoh; Muhammad Ichsan; Ria yunita (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In conducting business, it is important to strengthen brand awareness among consumers as this can be key to influencing them to visit the company for the first time and to return. This study analyzes the strategy of utilizing Instagram social media as the main tool in building the corporate image of PT Suvarna Jakarta Golf Club using a qualitative descriptive approach to gain an in-depth understanding. The aim of this research is to understand the contribution of social media in shaping public perception and enhancing the company's image. Data were collected through interviews with company management and Instagram account managers, as well as through observation and documentation of posted content. The results of the study highlight effective strategies and challenges faced in utilizing this platform to strengthen the corporate image, providing valuable insights for marketing practitioners and researchers in this field..